The Impact of Pulsed Nd:YAG Laser Energy and Wavelength on Human Teeth Enamel: In Vitro Study - Tareq, Mays; Hamad, Tagreed; Al-abassi, Salam A. W. (Al-Nahrain Journal for Engineering Sciences, 2024)
The aim of the research was for evaluation the morphological and chemical alterations that result from the Nd:YAG laser treatment of dental enamels using optical microscopy (OM) with Energy dispersion X-ray spectroscopy (EDX), respectively. Two human enamel samples were obtained, the samples were exposed to the Nd: YAG laser irradiation. The micrographs obtained by optical microscopy demonstrated morphological changes. The concentrations of carbon (C), calcium (Ca), phosphorus (P), and oxygen (O) in crater sites and its environs were measured using EDX, as well as trace amounts of manganese, magnesium, and silicon. However, due to their low concentration, these trace elements were neglected. We obtained the maximum depth profile of carters on tooth enamel surface at 1200 µm with laser pulse of 532 nm with 500 mJ energy/pulse, while the minimum depth profile of carters at 200 µm with laser pulse of 1064 nm with 100 mJ energy/pulse. Dental tissue can be safely treated with a Nd: YAG laser with 200 mJ, 9 ns, and 1064 nm since this laser irradiation range did not induce any noticeable morphological changes. As a result, the Nd: YAG laser offers as an ideal option for clinical treatment.